Dynamics of spray granulation in continuously operated horizontal fluidized beds - Neugebauer, C.; Diez, E.; Mielke, L.; Palis, S.; Bück, Andreas; Tsotsas, E.; Kienle, A.; Heinrich, S. (Dynamic Flowsheet Simulation of Solids Processes, 2020)
This chapter presents new findings on process and product design in continuous spray layering granulation in horizontal fluidized beds. The results are achieved by a multi-scale approach, combining single-particle characterization of the influence of drying conditions on layer formation and properties with meso-scale information of particle flowand recirculation between process chambers separated by weirs. On the macro-scale, population balance modeling is used to describe the overall process dynamics taking into account apparatus design and process conditions. New process regime maps are presented along with control concepts to guarantee stable and safe operation as well as desired particle properties.
CRIS-Team Scopus Importer:2020-08-28